A numerical simulation study of hydrogen-air mixture combustion in a closed chamber at low initial pressure - Oleh Tryfonov; Olga Shypul; Vadym Garin; Vitalii Myntiuk; Denys Tkachenko (Радіоелектронні і комп'ютерні системи)
This study investigates the combustion of a hydrogen-air mixture at low initial pressure in a closed chamber, focusing on thermal energy methods (TEM) used for processing thermoplastics. This study aims to develop and validate a numerical model capable of predicting critical combustion parameters, specifically, the pressure and temperature distribution profiles over time, to ensure safe and efficient TEM processing. The tasks included constructing and validating the hydrogen-air combustion model using experimental data for high accuracy and applicability in TEM systems. The methods involved numerical simulation of the hydrogen-air mixture combustion in ANSYS Fluent using the GRI-Mech 3.0 mechanism, employing fourth-degree polynomial functions to define the thermodynamic properties of the species. Validation against previous experimental data yielded highly accurate results with peak pressure deviations of less than 3%. The following validation, the model was applied to simulate combustion in an industrial TEM chamber, which is representative of real operational conditions. Results showed consistent flame front development, including the formation of turbulent cellular structures, which are essential for achieving optimal temperature distribution and stability within the chamber. These insights allow for strategic part placement to maximize processing quality, which is especially important when using low-pressure hydrogen-air mixtures. In conclusion, the validated model emphasizes the potential of green hydrogen-based fuels as eco-friendly alternatives for energy-intensive industrial processes, thereby advancing climate-neutral manufacturing. Future work will expand on combustion studies using plastic parts in TEM chambers to improve processing precision and safety for broader adoption in sustainable thermoplastics manufacturing.